EDUCATION POLICY ANALYSIS ON EDUCATION MARKETING - Heni Winarsih; Andi Nirmayanthi, Yuspiani, Wahyuddin Naro (CV. ADIBA AISHA AMIRA, 2024)
The research problem raised in this paper is to see how the analysi of education policy on education marketing. This research also aim to see how the impact of decentralisation policy on education i madrasah. This research is a qualitative research using a literatur study approach. Education policy analysis is closely related t efficiency and effectiveness in the world of education. This mean that policies in the aspects of process and implementation, whic must look at human resources, funds, facilities and policy benefits In this era of globalisation, competition has entered all aspects o life, including education. The world of education is required to b more creative and innovative in exploring the potential contained i these educational institutions. Educational institutions nee marketing to continue to exist and compete with other institutions